Design and Validation of a qPCR Panel for Stem Cell Differentiation - Lindblom, Linn (My University, 2016)
The purpose of this project was to develop and validate a qPCR panel for stem cells differentiation for human cells. The panel consists of 62 selected genes, which are marker for cell differentiation for neurons, cardiac cells, kidney cells, embryonic cells and detection of pluripotency. The validation of the panel implied design of assays, qPCR analysis with SYBR Green and probe, control of PCR product length with a capillary electrophoresis instrument and a preamplification. The assays were designed between an exon-exon junction or separated with large introns as far as possible. Some assays are designed over an exon, in order to detect as many protein coding transcript variants as possible. The selected genes have been analyzed successfully with SYBR Green and probe. A validation of a preamplification is performed to enable analysis of limited sample volumes. The preamplification implied a mixed pool consisted of all primers and reference genes. The solution was analyzed with a regular PCR analysis with SYBR Green. Products from the regular PCR was used as template in the final qPCR analysis. The results from the preamplification were good. Efficiency for the assays were ≥ 90 % for almost all assays and they were reproducible. So far, the panel is only validated for preamplification with SYBR Green. In the near future, the panel also will be validated with probe. The result of this project is a developed qPCR panel for stem cells differentiation for human cells. The qPCR based panel can now be used of scientists to detect the differentiation state of added stem cells.
Keywords: Livsvetenskaper; Biologiska vetenskaper; Life Science; Biological Sciences